2014
DOI: 10.1002/adma.201305659
|View full text |Cite
|
Sign up to set email alerts
|

Highly‐Efficient, Flexible Piezoelectric PZT Thin Film Nanogenerator on Plastic Substrates

Abstract: A highly-efficient, flexible piezoelectric PZT thin film nanogenerator is demonstrated using a laser lift-off (LLO) process. The PZT thin film nanogenerator harvests the highest output performance of ∼200 V and ∼150 μA·cm(-2) from regular bending motions. Furthermore, power sources generated from a PZT thin film nanogenerator, driven by slight human finger bending motions, successfully operate over 100 LEDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
539
3
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 748 publications
(558 citation statements)
references
References 33 publications
3
539
3
4
Order By: Relevance
“…52 On the contrary, our AD-formed KNN f-PEH device is strikingly superior to these representative previous reports of flexible lead-free generators. The high performance in this work is even comparable to that of prior high-performance lead-based f-PEHs made by sol-gel PZT films, 11,65 AD-formed PZT thick film, 55 and solid-grown Pb(Mg 1/3 Nb 2/3 )O 3 -PZT (PMN-PZT) thick film 66 with IDEs under similar deformations. This remarkable output performance of our lead-free f-PEH stems from the high-quality and dense AD-formed L-KNN piezoceramic thin film.…”
supporting
confidence: 70%
“…52 On the contrary, our AD-formed KNN f-PEH device is strikingly superior to these representative previous reports of flexible lead-free generators. The high performance in this work is even comparable to that of prior high-performance lead-based f-PEHs made by sol-gel PZT films, 11,65 AD-formed PZT thick film, 55 and solid-grown Pb(Mg 1/3 Nb 2/3 )O 3 -PZT (PMN-PZT) thick film 66 with IDEs under similar deformations. This remarkable output performance of our lead-free f-PEH stems from the high-quality and dense AD-formed L-KNN piezoceramic thin film.…”
supporting
confidence: 70%
“…An inorganic‐based laser lift‐off (ILLO) process was used in this method 40. The size limitation of PZT thin film was eliminated by the ILLO process, resulting in an output increase of the flexible PENG ( Figure 6 A).…”
Section: Materials and Device Designmentioning
confidence: 99%
“…Park et al demonstrated large-area PZT thin films on flexible substrates via a laser lift-off (LLO) process and fabricated a thin-film nanogenerator (NG) to realize highly efficient, lightweight, and flexible piezoelectric energy harvesting devices. (39) …”
Section: Transferring Process Of Piezoelectric Thick Filmmentioning
confidence: 99%
“…(32) (c) Final flexible PZT thin-film NG attached to a glass tube and bent by human fingers (inset) (d) (i) Open-circuit voltage and cross-sectional current density measured from PZT thin-film NG and (ii) Measured output voltage and cross-sectional current density under different load resistances from 2 kΩ to 1 GΩ. (39) in vivo biomechanical energy. (54) This single-crystal harvester generated a short-circuit current of 1.75…”
Section: Energy Harvesters With Flexible Polymer Substratementioning
confidence: 99%